Evaluation of a national supermarket intervention supporting vulnerable families in healthy meal practices: a natural experiment - Marjolijn Vos; Viktor L. J. Proesmans; Anneleen Van Kerckhove; Benedicte Deforche; Nathalie Michels; Maartje P. Poelman; Wendy Van Lippevelde (BMC Medicine)
Abstract Background Lower socioeconomic status (SES) is linked to diets that do not meet dietary guidelines. The “Dinner is served at 1-2-3 euros” (DS123) supermarket intervention aims to support vulnerable families in cooking more home-made meals, combining food literacy strategies and price incentives. This study evaluated its impact on food purchases. Methods Food purchase data (total number of product purchases, n = 260,214) from participating families with lower SES (n = 134) were analyzed over a period of four and a half years, using a longitudinal within-group pre-post design. Binomial generalized linear mixed models assessed changes in the proportion of total food budgets spent on vegetables, prepackaged meals, and sweet and salty snacks. Results Enrollment in the intervention resulted in higher odds of spending money on vegetables than on other categories (OR = 1.119, 95% confidence interval (CI): 1.082, 1.157; p < 0.001), while it resulted in lower odds spending on prepackaged meals (OR = 0.810; 95% CI: 0.774, 0.848; p < 0.001) and on sweet and salty snacks (OR = 0.851; 95% CI: 0.828, 0.875; p < 0.001). Additionally, more purchased products of the recipe booklets during the intervention period (i.e., higher adherence) led to similar changes in the relative share of budget being spent on vegetables (OR = 1.089; CI: 1.084, 1.095; p < 0.001), prepackaged meals (OR = 0.934; CI: 0.924, 0.943; p < 0.001), and on sweet and salty snacks (OR = 0.965; CI: 0.960, 0.970; p < 0.001). Conclusions The DS123 intervention improved food purchasing patterns in families with lower SES, increasing spending on vegetables while reducing spending on prepackaged meals and snacks. Price incentives combined with food literacy strategies show promise in enhancing healthy dietary behaviors in vulnerable families. Trial registration The study protocol was pre‑registered prior to data collection at ClinicalTrials.gov (NCT05595551—27/10/2022).